Optimum selenium levels in diets high in plant‐based feedstuffs for gilthead sea bream (Sparus aurata) fingerlings. (1st December 2019) - Domínguez, David; Sehnine, Zakarya; Castro, Pedro; Robaina, Lidia; Fontanillas, Ramon; Prabhu, Philip Antony Jesu; Izquierdo, Marisol
Abstract: Substitution of marine ingredients (FM‐FO) by plant protein and oil sources can modify selenium (Se) levels in feeds. Se plays an important role in the antioxidative defence by forming part of selenoproteins. Se requirements of gilthead sea bream are not accurately determined; therefore, this study was conducted to define Se supplementation levels in low FM‐FO practical diets for sea bream fingerlings. A plant‐based diet containing 0.45 mg Se/kg diet was used as the basal diet. Four other diets were supplemented to contain 0.68, 0.86, 1.00 or 1.70 mg Se/kg diet, supplied as sodium selenite. Sea bream, weighing 12.6 ± 1.4 g, were distributed in triplicate groups per diet and fed for 42 days. Se supplementation up to 1.00 mg Se/kg significantly improved the growth of sea bream, whereas further increase up to 1.70 mg Se/kg diet reduced growth. The results of this study suggest that the optimum dietary levels of sodium selenite in diets with low FM‐FO with basal levels of 0.45 mg Se/kg are around 0.94 mg Se/kg to promote growth of gilthead sea bream juveniles. On the contrary, dietary levels of 1.70 mg Se/kg were found to be excessive and caused growth reduction, increased catalase expression and hydropic degeneration in the liver.